Avaliação de déficit cognitivo em pessoas vivendo com HIV/AIDS em uso de terapia antirretroviral: estudo de série de casos - BASTOS, Vanessa Giovana da Costa (2023)
People living with HIV/AIDS still face challenges associated with the senescence process, with a greater susceptibility to develop neurocognitive deficits. This study aimed to evaluate the cognitive deficit in people living with HIV/AIDS using antiretroviral therapy treated at a referral hospital in Belém do Pará. A case series was described, with a qualitative and quantitative approach, in 60 patients over 18 years of age, using ART, in which three functional scales were applied: International HIV Dementia Scale; Instrumental Scale for Activities of Daily Living; and Mini Mental State Examination test. Of the total, 58 patients underwent IHDS and IADL, 81.03% had cognitive changes with a significant age difference (p=0.025) and older age in this group (mean 59 years and SD±8,9). Fifty-six patients underwent MMSE, 42.85% with alterations, significant age difference (p=0.025) and older age in this group (mean 60 years and SD±10.9). In the multivariate logistic regression analysis, age was a risk factor for the development of MMSE alterations (p=0.034, OR=1.069, 95%CI= 1.005-1.130) and physical activity was an independent protective factor (p= 0.017, OR=0.168, 95%CI=0.038-0.721): in the case group 12.5% performed physical activity and in the control group 53.1%. It was concluded that the applied scales are an important cognitive screening tool for HIV patients using ART, acting as an indicator of the patient's functional and cognitive status.